Изменение содержания витамина А в печени вечерницы рыжей и нетопыря-карлика в период зимней спячки в условиях Закарпатской области - Крочко, Ю.И.; Семистрок, Л.Д. (Вестник зоологии, 1973)
When comparing content of vitamin A in liver of Nuctalus noctula S c h r e b e r and Pipistrellus pipistrellus S c h r e b e r in different periods of hibernation it was established Mat its content is higher at the beginning of bats' hybernation, therewith in the liver of more active species P. pipistrellus vitamin A content is higher. In females of N. noctula S c h r e b e r for the whole period of hybernation vitamin .A content is higher than in males. In males of Pipistrellus pipistrellus S c h r e b e r at the beginning of hybernation axerophtol content in liver is greater, than in males and at the end of hybernation it is greater in females which is explained by thrifty expenditure of the vitamin that ensure the progeny viability.